UTILIZATION OF COPPER WEIGHT METAL ION (II), KROMIUM (III), TIMBAL (II), AND SENG (II) IN LIQUID WASTE INDUSTRY FOR ELECTROPLATING IRON COATING - Siti Marwati; Regina Tutik Padmaningrum; Marfuatun Marfuatun (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2009)
This Research aim to know: 1) the potential difference which can degrade the heavy metal ion concentration of Cu(II), Cr(III), Pb(II), and Zn(II) in liquid waste of electroplating maximally, 2) the efficiency of degradation of heavy metal ions concentration of Cu(II), Cr(III), Pb(II), and Zn(II) in liquid waste of electroplating at optimal potential difference, and 3)the potential difference yielding the nicest coat quality pursuant to its physical appearance.This research early with the preparation electroplating: 1) the preparation of sample liquid waste, 2) platinum electrode,and 3) iron metal to be arranged in layers. The instrument of this research is potentiometers Shimadzu NES_5F. Process the electroplating has been done at variations of potential difference that are 2.0; 2.5; 3.0; 3.5; 4.;, 4.5; and 5.0 V. Analysis of concentration of metal ions in liquid waste of electroplating before and hereafter process the electroplating have been done by atomic absorbtion spectrophotometric (AAS). Perception result of coating have been done visually by researcher. The result of this research are 1) the potential differences which can degrade the heavy metal ions concentration of Cu(II), Cr(III), Pb(II), and Zn(II) in liquid waste of electroplating maximally is 4 V, 2) efficiency of degradation of heavy metal ions concentration of Cu(II), Cr(II), Pb(II), and Zn(II) in liquid waste of electroplating at optimal potential difference successively are 21.30; 72.37; 51.00; and 58.60 %, and 3) potential difference yielding the nicest coat quality pursuant to its physical appearance is 4 V.